Komodifikasi Religiusitas: Pandangan Aktifis Islam Kota Medan terhadap Tayangan Religius di Televisi - Iswandi Syahputra (Jurnal Komunikasi, 2007)
This article is based on a field research. The research was conducted in Medan, February 2007. The main objective of the research is to understand, analyze, and describe the opinion of Islamic activists in Medan toward religious television program. Religious television program is a television program which contains Islamic syiar (dakwah Islamiyah) and presented using various programs, such as lecture, television movie, music show, talk show, or dai contest This research used critical paradigm with qualitative approach by using deep interview technique toward 15 Islamic activists in Medan. The choice of these subjects is based on his/her structural position in certain religious organization or his/her activity in Islamic syiar (dakwah Islamiyah). This research shows that the subjects consider television has two faces, which is giving benefit and disadvantage (mudharat) in the same time. This opinion had lead toward a discussion of the law of watching television (is it halal or haram?). Although it has benefit, the religious television program is considered ineffective in giving influence toward Islamic religious life, because it is not reflecting lslam as a religion.